Analysis of Okun’s Law in Eurozone Countries - Šímová, Zuzana Alžběta; Ruschka, Adam; Jordán, Lukáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines the validity of Okun's Law in the euro area during the post-financial crisis period. The theoretical section outlines Okun's Law and its various versions, reviews recent empirical literature, presents key critiques, and considers the specific context of the pandemic years. The empirical analysis employs both gap and difference specifications for the euro area as a whole using panel regressions, while country-level estimates are obtained using Ordinary Least Squares with the gap version. All models are estimated over two periods: the first spans from 2009 to 2019 and excludes the pandemic years, while the second covers the full period from 2009 to 2024. The results suggest that Okun's Law generally holds within the euro area, though the relationship weakened during the pandemic and exhibits significant cross-country variation. This study contributes to the existing literature by offering a detailed overview of the different formulations of Okun's Law, including Okun's original estimates, and by integrating multiple empirical approaches that also capture the impact of the COVID-19 pandemic.
Vedoucí práce: Adam Ruschka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses